(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
The autonomic nervous system (ANS) controls involuntary body functions such as heart rate, digestion, and respiration. It consists of two parts: the sympathetic nervous system (SNS) and parasympathetic nervous system (PNS). The SNS triggers the “fight or flight” response during stress by increasing heart rate, dilating pupils, and redirecting blood to muscles. The PNS promotes rest and recovery. The ANS originates from the brainstem and spinal cord. Under stress, the SNS releases adrenaline and noradrenaline to prepare the body for action. Chronic stress disrupts the balance between SNS and PNS, leading to health problems like hypertension and anxiety. Understanding ANS anatomy and stress response is important for managing stress-related disorders.